Negativicoccus succinicivorans gen. nov., sp. nov., isolated from human clinical samples, emended description of the family Veillonellaceae and description of Negativicutes classis nov., Selenomonadales ord. nov. and Acidaminococcaceae fam. nov. in the bacterial phylum Firmicutes - Marchandin, Hélène; Teyssier, Corinne; Campos, Josiane; Jean-Pierre, Hélène; Roger, Frédéric; Gay, Bernard; Carlier, Jean-Philippe; Jumas-Bilak, Estelle (International journal of systematic and evolutionary microbiology, 2010)
Three strains of a hitherto unknown, Gram-negative, tiny, anaerobic coccus were collected from human clinical samples originating from skin and soft tissues. The three isolates displayed at least 99.9 % identity in their 16S rRNA gene sequences and more than 99.8 % identity in their dnaK gene sequences. The isolates were affiliated to the family Veillonellaceae , the coccobacillus Dialister micraerophilus being the most closely related species, but there was no more than 91.1 % identity in the 16S rRNA gene sequence between this species and the three isolates. Phylogeny based on the 16S rRNA gene confirmed that the three strains represent a novel and robust lineage within the current family Veillonellaceae . A similar genomic structure was demonstrated for the three isolates by PFGE-based analysis. Morphology and metabolic end products, as well as genotypic and phylogenetic data supported the proposal of the novel genus Negativicoccus gen. nov., with the novel species Negativicoccus succinicivorans sp. nov. [type strain ADV 07/08/06-B-1388 T (=AIP 149.07 T =CIP 109806 T =DSM 21255 T =CCUG 56017 T ) as type species]. Phylogenetic analyses based on the 16S rRNA gene sequences of members of the phylum Firmicutes and other phyla indicated that the family Veillonellaceae forms a robust lineage clearly separated from those of the classes ‘ Bacilli ’, ‘ Clostridia ’, Thermolithobacteria and ‘ Erysipelotrichi ’ in the phylum Firmicutes . Therefore, we propose that this family is a class-level taxon in the phylum Firmicutes , for which the name Negativicutes classis nov. is proposed, based on the Gram-negative type of cell wall of its members, with the type order Selenomonadales ord. nov. In this order, a novel family, Acidaminococcaceae fam. nov., is proposed and description of the family Veillonellaceae is emended.